2021
DOI: 10.3390/molecules26165003
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Evaluation of Alginate/Bacterial Cellulose Nanocrystals–Chitosan–Gelatin Composite Scaffolds

Abstract: It is common knowledge that pure alginate hydrogel is more likely to have weak mechanical strength, a lack of cell recognition sites, extensive swelling and uncontrolled degradation, and thus be unable to satisfy the demands of the ideal scaffold. To address these problems, we attempted to fabricate alginate/bacterial cellulose nanocrystals-chitosan-gelatin (Alg/BCNs-CS-GT) composite scaffolds using the combined method involving the incorporation of BCNs in the alginate matrix, internal gelation through the hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 53 publications
2
36
0
Order By: Relevance
“…The homogeneous alginate composite hydrogels were fabricated via physical blending and alternating electrostatic assembly technology with the HAP/GDL complex as the endogenous cross-linking agent according to our previous method [ 29 , 30 ]. In the ion cross-linking of alginate, the cross-linking rate is the key factor to control the gel uniformity and strength.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The homogeneous alginate composite hydrogels were fabricated via physical blending and alternating electrostatic assembly technology with the HAP/GDL complex as the endogenous cross-linking agent according to our previous method [ 29 , 30 ]. In the ion cross-linking of alginate, the cross-linking rate is the key factor to control the gel uniformity and strength.…”
Section: Resultsmentioning
confidence: 99%
“…Composite hydrogels prepared by electrostatic assembly and physical blending of biomacromolecules could significantly inhibit the swelling property of ALG Gel, enhancing its stability in saline solution. It was found that Alg-CS-GT had the best control of the swelling behavior, which was due to the formation of a dense polyelectrolyte complex during the electrostatic assembly process, which effectively restrained the swelling of composite hydrogels [ 30 ]. However, when the composite hydrogel was immersed in PBS for more than 12 h, ALG/GT-CS exhibited higher swelling due to the strong hydrophilicity of GT, which resulted in the continuous swelling of the material.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alg, like chitin and chitosan, is frequently employed for bone tissue engineering [ 16 ]; for example Alg hydrogels are employed as fillers and carriers of osteoinductive factors [ 17 , 18 ]. This is due to the fact that Alg has several desirable characteristics, including water solubility, biocompatibility, low toxicity, low cost, extended active agent release and moderate and quick hydrogelation when divalent cations, such as Ca 2+ , are added [ 18 , 19 , 20 , 21 ]. However, natural polymers such as Alg have limits due to mechanical qualities that are insufficient to be used in bone tissue engineering [ 17 , 18 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the fact that Alg has several desirable characteristics, including water solubility, biocompatibility, low toxicity, low cost, extended active agent release and moderate and quick hydrogelation when divalent cations, such as Ca 2+ , are added [ 18 , 19 , 20 , 21 ]. However, natural polymers such as Alg have limits due to mechanical qualities that are insufficient to be used in bone tissue engineering [ 17 , 18 , 20 , 21 ]. To address these issues, a variety of materials, such as nanomaterials, have been mixed into the alginate structure, resulting in strong composite materials [ 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%